2011
DOI: 10.1080/15222055.2011.579033
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Tissue Fatty Acid Composition of Rainbow Trout Reared on Feeds Containing Fish Oil or Equal Blends of Fish Oil and Traditional or Novel Alternative Lipids

Abstract: Fish oil (FO) sparing is common in aquafeed formulation; however, some alternative lipids have proven to be more successful than others in ensuring adequate growth and maintenance of desirable fillet fatty acid (FA) composition. Depending on the lipids used, grow‐out feeds influence the FA composition of the tissues of “lean‐fleshed” fishes and their responsiveness to subsequent tailoring during finishing. To address whether different lipid sources similarly influence growth performance and tissue composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
8
28
1
Order By: Relevance
“…Fish oil sparing rarely impacts fish production performance as long as essential fatty acid requirements are met (Turchini et al , 2011aGao et al 2011;Trushenski et al 2011aTrushenski et al , 2011bTrushenski et al , 2011cTrushenski et al , 2011dTrushenski et al , 2013aTrushenski et al , 2013bKamarudin et al 2012;Mulligan and Trushenski 2013;Ng et al 2013;Trushenski and Kanczuzewski 2013). Our results are consistent with this convention and with other research on fish oil sparing in Cobias (Trushenski et al 2011a(Trushenski et al , 2012(Trushenski et al , 2013bWoitel et al 2014).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Fish oil sparing rarely impacts fish production performance as long as essential fatty acid requirements are met (Turchini et al , 2011aGao et al 2011;Trushenski et al 2011aTrushenski et al , 2011bTrushenski et al , 2011cTrushenski et al , 2011dTrushenski et al , 2013aTrushenski et al , 2013bKamarudin et al 2012;Mulligan and Trushenski 2013;Ng et al 2013;Trushenski and Kanczuzewski 2013). Our results are consistent with this convention and with other research on fish oil sparing in Cobias (Trushenski et al 2011a(Trushenski et al , 2012(Trushenski et al , 2013bWoitel et al 2014).…”
Section: Discussionsupporting
confidence: 95%
“…Specifically, differences in fillet LC-PUFA content persisted through harvest, and there was no significant effect of time (i.e., the duration of finishing) on fillet LC-PUFA level; in addition, C 18 PUFA levels increased significantly in all fillet and eye tissues and in some liver tissues during finishing. It has been suggested that C 18 PUFAs are somewhat resistant to change during finishing (Thanuthong et al 2011;Trushenski et al 2011b), but we believe that in the present case these trends are more likely related to differences in fatty acid composition among different batches of finishing feed (Table 3). Batches of the finishing feed were assembled independently and at disparate times.…”
Section: Discussioncontrasting
confidence: 54%
“…For example, in Rainbow Trout Oncorhynchus mykiss, feeding diets containing 50:50 blends of fish oil and beef tallow, pork lard, poultry fat, fully or partially hydrogenated soybean oil, fully hydrogenated cottonseed oil, palm oil, or coconut oil resulted in fillet D jh values of approximately 4-11, whereas feeding 50:50 blends of fish oil and soybean or canola oils resulted in D jh values of approximately 14-17 (Trushenski et al 2011a(Trushenski et al , 2011c. A review of the literature on fish oil sparing in Rainbow Trout indicated similar, high D jh values for fish fed blends of other C 18 PUFA-rich vegetable oils, including sunflower and soybean oils (Gause and Trushenski 2013).…”
Section: Discussionmentioning
confidence: 94%
“…To increase shelf stability or alter the physical characteristics of soybean oil, it is common for it to be partially or fully hydrogenated to decrease C 18 PUFA levels. The hydrogenation process increases MUFA and SFA content, and hydrogenated soybean oils have shown promise as tissue profile-conserving alternatives to fish oil in aquafeeds (Laporte and Trushenski 2011;Trushenski et al 2011aTrushenski et al , 2013aMulligan and Trushenski 2013;Woitel et al 2014a). More recently, hydrogenation has fallen out of favor as health and nutrition professionals and the general public have become aware of the hazards of trans fats generated by the hydrogenation process (Brown and Hart 2011).…”
mentioning
confidence: 98%
See 1 more Smart Citation